Analisis mengenai berbagai faktor yang memengaruhi nasabah dalam memilih asuransi syariah - Ramadhoni, Nurul (Maliki Interdisciplinary Journal, 2025)
This article aims to analyze the growth of sharia insurance in Indonesia as well as various factors that influence people’s choice of sharia insurance. The sharia insurance industry in Indonesia has experienced significant progress in recent years, marked by an increase in assets and the number of companies involved. Sharia insurance offers various advantages such as transparency, fairness and a profit sharing system that is in line with Islamic principles, making it increasingly popular among Muslim communities. However, despite the many benefits, there are challenges such as a longer claims process and limited product coverage. For this reason, this article also discusses the importance of education and outreach to the public, as well as strategies that can be implemented by sharia insurance companies, such as effective promotion and improving service quality, to increase public awareness and participation in sharia insurance. Therefore, it is hoped that this article can provide an understanding regarding the development of sharia insurance and efforts to encourage its further growth in Indonesia.